Rasionalitas Sosial-Ekonomi Masyarakat Muslim Glagah: Studi Kasus New Yogyakarta International Airport Di Kulon Progo, D. I. Yogyakarta - Muchamad Agus Munir; Ilyasi - (Empower : Jurnal Pengembangan Masyarakat Islam, 2020)
This study aims to describe and provide understanding that the construction of the New Yogyakarta International Airport is a conflict of interest between the government and capital owners with local Muslim communities. The conflict created a social space that was different from the socio-historical space of the local community. The method used in this research is field research with a sociological approach, primary data sources for interviews, observation and documentation, secondary data with books, journals and websites, and data analysis techniques using content analysis. The time spent in research is around 3 months, March-May 2019. The results of the study show that with the development of NYIA, a new social space was formed which according to Henry Lavebre's theory is, (1) Spatial Practices and Construction of City-Based Development, meaning that there is a change in life around the airport is especially related to capital owners. They will be free to control and determine life. (2) Construction and Contestation of Economic Development, the intention is a change in economic terms, from traditional to modern. (3) Abstract Space Glagah Village, a capitalization that is not realized by the local community, especially in the economic, political and lifestyle fields. (4) NYIA Space Contradiction, uncertainty for the lower middle class in the pattern of life, this is due to more control by capital owners. (5) Reproduction of Religious Spaces. Only people who have power over places of worship can obtain or have the right to manage and utilize religious facilities collected under the pretext of caring for and developing religion around the airport.